1987
DOI: 10.3109/00207458708985928
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Evoked Potential Generators: Current Source-Density Analysis of Visually Evoked Potentials in the Cat Cortex

Abstract: The depth profiles of visually evoked field potentials were recorded in areas 17 and 18 of the cat visual cortex. For comparison, potential profiles evoked by electrical stimulation of the primary afferents and of the nonspecific reticular system were also recorded. From these profiles the current source-density (CSD) distributions were calculated using the one-dimensional CSD method. CSD distributions evoked by the different types of stimuli differ in their amplitudes and time courses by approximately one and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
171
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(186 citation statements)
references
References 68 publications
12
171
3
Order By: Relevance
“…During every trial we simultaneously recorded field potentials, which reflect integrated synaptic activity (Mitzdorf, 1987). The response location was identified by 569 nm optical imaging, and a burr hole drilled in the thinned skull near the activation center.…”
Section: Electrophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…During every trial we simultaneously recorded field potentials, which reflect integrated synaptic activity (Mitzdorf, 1987). The response location was identified by 569 nm optical imaging, and a burr hole drilled in the thinned skull near the activation center.…”
Section: Electrophysiologymentioning
confidence: 99%
“…By recording field potentials simultaneously with hemodynamic signals, we obtained a measure of synaptic activity evoked by the stimulation, since field potentials are thought to reflect the weighted sum of postsynaptic currents (Mitzdorf, 1987). The degree to which hemodynamic responses propagate both retrograde and anterograde increases with increasing synaptic activity.…”
Section: Neurovascular Couplingmentioning
confidence: 99%
“…Evidence for their origin was often gathered from current-source density (CSD) analysis and combined field potential and intracellular recordings (Mitzdorf 1985;Nadasdy et al 1998). Mitzdorf suggested that LFPs actually reflect a weighted average of synchronized dendrosomatic components of the synaptic signals of a neural population within 0.5-3 mm of the electrode tip (Juergens et al 1999;Mitzdorf 1987). Later studies, however, provided evidence of the existence of other types of slow activity unrelated to synaptic events, including voltage-dependent membrane oscillations (e.g., Kamondi et al 1998) and spike afterpotentials.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of viewing the cortex as a single network, we now conceive of the cortical laminae as a stack of loosely interconnected but distinct neuronal networks (1)(2)(3)(4)(5). Each lamina has different specific inputs, projection targets, and feedback connections.…”
mentioning
confidence: 99%